Fair Scheduling in Broadcast Environments - Bahl, Victor; Vaidya, Nitin H. (1999)
This report considers the problems of scheduling transmissions in broadcast environments, including, wireless environments. Issues that affect the design of fair scheduling algorithms, and several alternative approaches to implementing fair scheduling in single-hop and multi-hop environments are identified.